The landscape of theoretical physics : a global view : from point particles to the brane world and beyond in search of a unifying principle - Pavšič, Matej (Fundamental theories of physics, 2001)
This book attempts to provide a synthetic view of fundamental theoretical physics. It describes the ingredients which may have to be used in order to build a theory which will unify general relativity, quantum field theory, and the known fundamental interactions. The books written so far have either considered a specialized topic in much detail, or they were too superficial and general. This book unites both approaches: it provides enough detail to start with, but does not go too far in developing a particular special field. Instead it turns to another special field and then shows how different fields are interrelated in a fascinating way. Many surprising new findings are revealed. Audience: This book will be of interest to those who would like to explore how the `Theory of Everything' could possibly be formulated. It will be of interest to researchers and students. A background in general relativity and quantum mechanics is recommended. The introductory sections, and especially Part IV: Beyond the Horizon, need no such background knowledge. They are intended for the reader who is interested in the conceptual and even philosophical questions.